ANALISIS INTELECTUAL CAPITAL DAN KINERJA PERBANKAN SYARIAH DI INDONESIA: Studi Pada Bank Umum Syariah - Sari Putri Pertiwi; Tb Ismail; Fauji Sanusi (Gapenas Publisher, 2021)
Intelectual capital is one of the instruments that can determine the value of the company. This study aims to find out and test the influence of the intellectual capital components (VACA, VAHU and STAVA) as well as their changes (ROGIC) on the company's performance (ROA and ROE). The object of the study is 13 Sharia Commercial Banks in Indonesia with a period of financial statements in 2013-2017. Data processing and analysis using the help of SPSS application version 19.00 with multiple linear regression models. Based on the results of hypothesis tests obtained VACA has no significant effect on the company's performance, VAHU has a negative and significant effect on the company's performance, STAVA has a positive and significant effect on the company's performance, ROGIC has a significant negative effect on the company's performance